Structural and computational study on inhibitory compounds for endonuclease activity of influenza virus polymerase. Issue 17 (1st September 2015) - Fudo, Satoshi; Yamamoto, Norio; Nukaga, Michiyoshi; Odagiri, Takato; Tashiro, Masato; Neya, Saburo; Hoshino, Tyuji
Graphical abstract: Abstract: Seasonal epidemics and occasional pandemics caused by influenza viruses are global threats to humans. Since the efficacy of currently approved drugs is limited by the emerging resistance of the viruses, the development of new antiviral drugs is still demanded. Endonuclease activity, which lies in the influenza polymerase acidic protein N-terminal domain (PAN ), is a potent target for novel antiviral agents. Here, we report the identification of some novel inhibitors for PAN endonuclease activity. The binding mode of one of the inhibitory compounds to PAN was investigated in detail by means of X-ray crystal structure analysis and molecular dynamics (MD) simulation. It was observed in the crystal structure that three molecules of the same kind of inhibitor were bound to one PAN . One of the three molecules is located at the active site and makes a chelation to metal ions. Another molecule is positioned at the space adjacent to the metal-chelated site. The other molecule is located at a site slightly apart from the metal-chelated site, causing a conformational change of Arg124. The last binding site was not observed in previous crystallographic studies. Hence, the stability of inhibitor binding was examined by performing 100-ns MD simulation. During the MD simulation, the three inhibitor molecules fluctuated at the respective binding sites at different amplitudes, while all of the molecules maintained interactions with the protein. Molecular mechanics/generalized Born surface area (MM/GBSA) analysis suggested that the molecule in the last binding site has a higher affinity than the others. Structural information obtained in this study will provide a hint for designing and developing novel potent agents against influenza viruses.